ROBUST CONTROL SYSTEM DESIGN FOR NETWORKED CONTROL SYSTEMS - ARIFIN , IMAM
Application of communication networks already increased for many field of area, including for control system. There are many advantages for this application. It also has several disadvantages that decreased system performance, then it is a contradiction with control system design objective, to improve system performance. That constraints must be minimized through considering them when designing the control system. Packet losses and delay will be considered in this research. Based on the properties of robust control (H8, H2 dan passivity), will be designed a robust control system for networked control system (NCS). NCS will be modeled using remote control system (Markov Jump Linear Systems) and designing will be formulated using Linear Matrix Inequality (LMI). In this research, state feedback case and output feedback case will be considered. Robust control system design for NCS result in a Bilinear Matrix Inequality (BMI), so that it can changed to an LMI using Schur complement, congruence transformation and change of variable controller. Simulation result shown that the robust control system for NCS can do system stabilization.